2015
DOI: 10.1177/1079063215612443
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy Checklist–Revised Use and Reporting Practices in Sexually Violent Predator Evaluations

Abstract: We surveyed evaluators who conduct sexually violent predator evaluations ( N = 95) regarding the frequency with which they use the Psychopathy Checklist-Revised (PCL-R), their rationale for use, and scoring practices. Findings suggest that evaluators use the PCL-R in sexually violent predator cases because of its perceived versatility, providing information about both mental disorder and risk. Several findings suggested gaps between research and routine practice. For example, relatively few evaluators reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
(108 reference statements)
1
40
0
Order By: Relevance
“…Additionally, in the majority of reviewed cases, psychopathy was used by the prosecution in an attempt to secure a conviction (Walsh & Walsh, 2006). Similar results have been found in other studies in both the United States and Canada, with the PCL-R being used to inform decisions of future dangerousness during sentencing and parole hearings (DeMatteo et al, 2014;Guy et al, 2015;, inform death penalty decisions in the States (DeMatteo et al, 2014), dangerous offender hearings in Canada (Blais & Forth, 2014b;Edens et al, 2014), and sexually violent predator hearings in the United States (Boccaccini et al, 2017;DeMatteo & Edens, 2006;DeMatteo et al, 2014).…”
Section: Psychopathy In the Criminal Justice Systemsupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, in the majority of reviewed cases, psychopathy was used by the prosecution in an attempt to secure a conviction (Walsh & Walsh, 2006). Similar results have been found in other studies in both the United States and Canada, with the PCL-R being used to inform decisions of future dangerousness during sentencing and parole hearings (DeMatteo et al, 2014;Guy et al, 2015;, inform death penalty decisions in the States (DeMatteo et al, 2014), dangerous offender hearings in Canada (Blais & Forth, 2014b;Edens et al, 2014), and sexually violent predator hearings in the United States (Boccaccini et al, 2017;DeMatteo & Edens, 2006;DeMatteo et al, 2014).…”
Section: Psychopathy In the Criminal Justice Systemsupporting
confidence: 63%
“…Intensifying the problem, case law reviews have indicated that the admissibility of expert mental health evidence about psychopathy is rarely challenged and, in the few cases where it is challenged, it is rarely objected to on the basis of undue prejudice even considering the association between psychopathy and negative court outcomes (Boccaccini et al, 2017). Research has also suggested that the psychopathy label, among others, is used more frequently by the prosecution to paint a negative picture of the defendant (Edens & Cox, 2012).…”
Section: Psychopathy In the Criminal Justice Systemmentioning
confidence: 99%
“…9 This training and infrastructure is crucial to for evaluators to attain minimum quality standards, as forensic evaluations are often complicated, requiring evaluators to consider difficult psychological, legal, and cultural nuances. 15,17,[42][43][44] Simply expanding the pool of eligible evaluator disciplines runs the serious risk of experts offering poorly formulated opinions, unless enough forensic training and infrastructure within that discipline exists.…”
Section: Qualitymentioning
confidence: 99%
“…A now well-established threat to reliability is bias of the evaluator toward the side that retained his/her services. 15,17,19 This "adversarial allegiance" effect is present even when evaluators score objective, structured risk assessments designed to mitigate subjective bias. 49 Earlier research has suggested evaluators' opinions are also influenced by the fees they earn.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation